Penghayatan Firasat Dalam Al-Quran dan Hadis, Dimensi Kerohanian, Fisiognomi, Perubatan, Pengadilan, Objek Budaya dan Karya Sastera Orang Melayu: Practice of Firasat in the Quran and Hadith, Spiritual Dimensions, Physiognomy, Medicine, Courts, Cultural Objects and Literary Works of the Malay People - Isa Kamari,; Abdul Hamid , Faisal @ Ahmad Faisal; Mohd Nor, Mohd Roslan (Journal Al-Muqaddimah, 2025)
Firasat (spiritual intuition) is practiced by the Malays in various dimensions of life: spiritual, physiognomy, medicine, administration of justice, cultural objects and literary works. Each of the practices of firasat in these dimensions demonstrates characteristics and aspects that are specific. This article analyses and develops a series of universal principles from the characteristics and aspects that are contextual in the practice of firasat.